Purification and Compression of Biogas: A Research Experience - Bajracharya, Tri Ratna; Dhungana, Alok; Thapaliya, Nirajan; Hamal, Gogan (Journal of the Institute of Engineering, 2009)
Biogas is widely used in villages of Nepal for cooking and lighting. But its commercial use has never been realized due to difficulties in its storage and transportation. Solution identified to the problem is to increase the energy density of the gas through removal of incombustible and corrosive gas and consequent compression which was experimented on a lab-scale model. This paper presents all the results of removal of CO2 gas from biogas using different chemicals and relative purity with raw gas. Further, compression of biogas and was carried out by methane refrigerant compressor and bottled into normal LPG cylinder. Compression of biogas was carried out under near Isothermal and Adiabatic conditions up to 11bar absolute pressure. The energy efficiency of compression was determined to be 98.71% and if the gas used for generation of electricity using a generator with an efficiency of 30%, the net energy efficiency turned out to be 95.72%. Later, a boiling test was conducted whereby the combustibility of the compressed biogas from the cylinder in normal biogas-stove was tested to validate its use in cooking, the results of which are included. Key words: Purification of Biogas, Compression of Biogas, Chemical purification, Energy efficiency, Combustion test. Journal of the Institute of Engineering, Vol. 7, No. 1, July 2009, pp. 90-98 doi: 10.3126/jie.v7i1.2066